The survey and analysis on the energy consumption of hospital buildings in Shandong province. (2017) - Gao, Zilong; Li, Yongan; Ning, Yu
Abstract: The paper made an actual investigation and survey surrounding the amount of hospital buildings in Shandong and energy consumption. At the same time, it gave a detailed analysis in terms of one certain hospital building in Jinan. In the aspect of amount of hospital buildings, the paper had a demonstration or analysis from these angles including the classification, rank, economic type, beds' amount and floorage about hospital. And get a conclusion that now the main point to save energy in Shandong is general hospital and special hospital of pubic hospital where the tertiary hospital is the first and secondary hospital and the following is the second. In the aspect of the survey of energy consumption on hospital buildings, make a quota of hospital buildings' energy consumption according to the investigated data, economy of every city and the feature to use energy of every city and so on. The paper carried out a field test of energy consumption, an evaluation of energy consumption and an analysis to energy conservation and made an estimation in allusion to the potential to save energy aiming at an actual hospital belonging to secondary hospital of general hospital in Jinan on the basis of obtained conclusions and quota.